Valores individuales y correspondencia organizacional (2019)
Ethics comes from the Greek ethos which means stay or place where you live. The Foundations of ethics require a broad definition to fully understand human behavior, which is responsible for forming habits and these are two that allow the development of personality and human behavior. Morality is a term which has similarity to ethics since it encompasses a set of rules established as rules of behavior which direct the individual´s daily behavior.